The knowledge, Attitude and Practice (KAP) of Syarikat Air Melaka Berhad’s (SAMB) employees on the acceptance of Key Performance Indicators (KPIS) as a performance measurement tool / Sylla Leeza Lee - Lee, Sylla Leeza (2010)
Key Performance Indicators (KPI) has been implemented at SAMB since 2009. It has been only 2 years since SAMB started implementing KPI as its performance measurement tool. As the system is still new to the company, this study aims to identify the knowledge, attitude and practices (KAP) of employees on the usage of KPI as a performance measurement tool. Systematic sampling method which involves drawing every 2nd element in the population was used to select 100 employees from a total of 206 Syarikat Air Melaka Berhad’s (SAMB) employees working specifically at Headquarters. The age of the respondents ranged mostly between 20 and 28 years, with a mean age of 3.8036. About 51% of the respondents were male, and 25% works in Jabatan Kewangan. A total of 21 (21%) respondents have worked with SAMB between 3 to 5 years and 87% of the total 100 samples respondents constitutes of non executive staff. Responses were gathered via combinations of self-administered instrument such as questionnaire and also through unstructured interviews. The findings showed that there is a positive relationship between knowledge (r = .371**), attitude (r = .323**), and practice (r = .225*) towards acceptance of KPI. This means that the higher the employees’ KAP, the higher their acceptance on KPI. In addition, the results revealed that knowledge is the highest predictor (B = .371) as acceptance of KPI in SAMB. This is mainly because, employees are given explanation before the implementation of KPI which makes them understand and aware of its purpose and objectives.